Título Padrão - Nunes, Vitória Gondim Real; Moura, Vanessa Paula Trigueiro (Passagens: Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal do Ceará, 2023)
The presence of women behind the camera as participants in the development of cinema has, throughout history, been obliterated and marginalized by narratives that place them in the position of mere objects and spectators. Such narratives are reinforced by the systematic erasure of women's production from film archives, which generally only present a vestige of the presence of women in the first decades of cinema. In this way, the present article proposes to discuss how the film archive was built over time and its relationship with this erasure of the presence of women in its production, in an attempt to claim the active role of women in a context of agency in the history of cinema and preserve memories more broader than those currently subjugated by dominant narratives.